Candes-Saint-Martin et ses cimetières : évolution de son organisation spatiale, depuis l’Antiquité jusqu’à l’époque Moderne (Région Centre, Indre-et-Loire) - Stéphanie Philippon; Matthieu Gaultier (Revue Archéologique du Centre de la France)
The supervision of sanitation work in the municipality of Candes-Saint-Martin, rue Trochet and in the locality les “Perrières”, realized in 2011/2012 by the Service de l’Archéologie du Conseil Général d’Indre-et-Loire, allowed to explore in a new way a surface of more than 2200 m2 in the center of the village.The indications of ancient occupations are very thin and brought only few new elements for the understanding of the organization of the secondary agglomeration.On the other hand, the data collected for the next periods (field data, history, archives, analysis of the built vestiges, in particular concerning two funeral large sets, allow us to raise a first sketch of the evolution of the spatial organization, since the Early Middle Ages (running VIIth century) till the end of the Modern period.